COMPETENCY OF HUMAN RESOURCES AND LOVE OF MONEY ATTITUDE IN MANAGEMENT OF FINANCIAL SMALL-MEDIUM MICRO BUSINESS - Saputra, Komang Adi Kurniawan; Ekajayanti, L.G.P. Sri; Anggiriawan, Putu Budi (Jurnal Reviu Akuntansi dan Keuangan)
This research explores the relationship between human resource competence and love of money attitude toward financial management of small and medium enterprises based on economic entity concept with moderated by knowledge management. This study proves that with the integration of several disciplines can help SMEs in managing their business, both from human resource management and accounting and financial management. This study uses a sample of 100 MSMEs engaged in the trade sector in Gianyar regency. Using MRA (Moderated Regression Analysis) method. The results of this study are the competence of human resources and attitudes of love of money affect the financial management based on economic entity concept. Further knowledge management is able to moderate the relationship between competence of human resources and attitude of love of money to financial management based on economic entity concept.